Mnemonic effects of action simulation from pictures and phrases - Ianì, Francesco; Foiadelli, Andrea; Bucciarelli, Monica (Acta psychologica, 2019)
Several theoretical approaches suggest that language comprehension and action observation rely on similar mental simulations. Granted that these two simulations partially overlap, we assumed that simulations stemming from action observations are more direct than those stemming from action phrases. The implied prediction was that simulation from action observation should prevail on simulation from action phrases when their effects are contrasted. The results of three experiments confirmed that, when at encoding the phrases were paired with pictures of actions whose kinematics was incongruent with the implied kinematics of the actions described in the phrases, memory for action phrases was impaired (Experiment 1). However, the reverse was not true: when the pictures were paired with phrases representing actions whose kinematics were incongruent with the kinematics of the actions portrayed in the pictures, memory for pictures portraying actions was not impaired (Experiment 2). Also, in line with evidence that simulations from action phrases and those from action observation partially overlap, when their effects were not contrasted their products were misrecognized. In our experiments, when action phrases only presented at recognition described actions depicted in pictures seen at encoding, they were misrecognized as had already been read at encoding (Experiment 1); further, when pictures only presented at recognition portrayed actions described in phrases presented at encoding, they were misrecognized as seen at encoding (Experiment 2). A third experiment excluded the possibility that the pattern of findings was simply a consequence of better memory for pictures of actions as opposed to memory for action phrases (Experiment 3). The implications of our results in relation to the literature on simulation in language comprehension and action observation are discussed. •A direct simulation mediates action observation whereas an indirect simulation is at stake in language comprehension.•When the effects of these two simulations were not contrasted their products were likely to be misrecognized.•However, when their effects were contrasted memory for action phrases but not memory for action photos was impaired.•Language comprehension and action observation rely on similar, but not identical, sensorimotor mental simulations.